America outdoors with Baratunde Thurston [videorecording (DVD)] (PBS, 2022)
It follows The New York Times bestselling author (How to Be Black), podcaster (How to Citizen with Baratunde), and outdoor enthusiast on his journey to explore the country's diverse landscapes and discover how they shape our outdoor lives. Wherever we live, we share a love for the wild, but in a country as big and diverse as America we have vastly different ways to find and experience nature. From coal miners turned beekeepers in Appalachia to Black surfers catching waves in L.A., this new series uncovers a deeper understanding of our passionate and complicated relationship with the natural world. It's an adventure that begins at a time of great change as the warming climate transforms our outdoor lives, shaping where we can go and what we can do in our wild spaces. As Baratunde investigates how these powerful forces are changing our outdoor lives, he meets a diverse group of Americans and discovers other forces of change like the drive to make sure the nation's natural wonders are accessible to all.